2014
DOI: 10.1371/journal.pone.0108434
|View full text |Cite
|
Sign up to set email alerts
|

EQ-5D-3L Derived Population Norms for Health Related Quality of Life in Sri Lanka

Abstract: BackgroundHealth Related Quality of Life (HRQoL) is an important outcome measure in health economic evaluation that guides health resource allocations. Population norms for HRQoL are an essential ingredient in health economics and in the evaluation of population health. The aim of this study was to produce EQ-5D-3L-derived population norms for Sri Lanka.MethodA population sample (n =  780) was selected from four districts of Sri Lanka. A stratified cluster sampling approach with probability proportionate to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
46
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 26 publications
23
46
3
2
Order By: Relevance
“…Overall, the Heilongjiang population had an average of EQ-5D-3L index score of 0.959, similar to the Singapore population norms (0.95) [37,38] and Taiwan population norms (0.946) [36], but higher than the norms reported in the USA (0.87) [31], Demark (0.889) [33], Sri Lanka (0.85) [39], and Japan (0.877) [40,41]. The mean VAS score of the Heilongjiang population (79.60) is only slightly lower than the national average (80.12) of China [24].…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Overall, the Heilongjiang population had an average of EQ-5D-3L index score of 0.959, similar to the Singapore population norms (0.95) [37,38] and Taiwan population norms (0.946) [36], but higher than the norms reported in the USA (0.87) [31], Demark (0.889) [33], Sri Lanka (0.85) [39], and Japan (0.877) [40,41]. The mean VAS score of the Heilongjiang population (79.60) is only slightly lower than the national average (80.12) of China [24].…”
Section: Discussionmentioning
confidence: 51%
“…A chronic condition was defined as a condition diagnosed by a doctor, for which either the symptoms persisted or relevant medical treatment continued over the past six months [24,38,39]. It was recorded as “yes” when a respondent had one or more of the chronic conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our sample did not include individuals aged 18-29 years, we observed that HRQoL decreases with age, reflecting the same trend observed in other studies. Our results indicate that men [1,12,17,23], younger people [1,23,30], people with a higher level of education [1,19,30], single people [30], people who practice physical activity and people with less time elapsed since T2DM diagnosis scored higher in the EQ-5D-3L and in the EQ-VAS.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, given the evolution of the disease to chronicity, its continuous monitoring in clinical practice is essential. HRQoL assessment helps to identify needs for new or revised health policies, the allocation of health resources, and strategic planning, while guiding and helping to improve the monitoring of the outcomes from community health interventions [19].…”
Section: Introductionmentioning
confidence: 99%